For colored girls who have considered suicide, when the rainbow is enuf a choreopoem - Shange, Ntozake (Scribner, 2010)
First published in 1975, Shange's choreopoem has been read and performed because it truly revealed what it meant to be of color and female in the twentieth century. Here is the complete text, with stage directions of the dramatic prose poem that resonates with unusual beauty in its fierce message to the world.